2016
DOI: 10.1111/coa.12576
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ingested foreign bodies according to age, type and location: a retrospective observational study

Abstract: The frequency of foreign body ingestion was highest in young children. However, we observed specific age-based characteristics that indicate specific precautions to take to avoid foreign body ingestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 18 publications
3
51
1
Order By: Relevance
“…Most studies in Asia and coastal countries reported that bone fragments, especially fish bones, are most commonly encountered. 3,12,13,16,18,24 While studies in the United States showed that meat comprised the majority type. 13,25 A systematic review including 13 092 patients all over the world revealed sharp-pointed FB (38.1%) as the most common FB.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in Asia and coastal countries reported that bone fragments, especially fish bones, are most commonly encountered. 3,12,13,16,18,24 While studies in the United States showed that meat comprised the majority type. 13,25 A systematic review including 13 092 patients all over the world revealed sharp-pointed FB (38.1%) as the most common FB.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign-body ingestion is a common encounter during pediatric emergencies or in general practice; importantly, however, it may lead to mortality [1][2][3][4][5]. The 2016 American Association of Poison Control Centers' National Poison Data System reported 1,810,030 incidents of foreign-body ingestion in a year [2].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign body ingestion (FBI) is often accidental ingestion of teeth, dentures, plastic, fish-or chicken bones in the elderly population (>65 years) [1]. However, in a study of Palta et al they investigated an adult population with a mean age of 45 years and found that 92% of the cases were intentional.…”
Section: Introductionmentioning
confidence: 99%